Vapour-liquid-solid growth of one-dimensional In2Se3 nanostructures and their promising field emission behaviour - Suryawanshi, Sachin R.; Bankar, Prashant K.; More, Mahendra A.; Late, Dattatray J. (RSC Advances, 2015)
Single crystalline ultra long In2Se3 nanowires have been grown by employing a single step facile thermal evaporation route under optimized conditions on Au/Si wafers, and morphology dependent field emission investigations on the In2Se3 nanostructure at the base pressure -1 x 10(-8) mbar are explored. In addition, structural and morphological analysis of as-synthesized In2Se3 nanostructures has been carried out using XRD, SEM and TEM. A plausible explanation of the vapor-solid-liquid (VLS) growth mechanism based on the experimental results and reported literature has been presented. Furthermore, field emission measurements demonstrate remarkably enhanced emission behaviour, which is explained on the basis of the field enhancement factor and aspect ratio of the nanostructures. The synthesized In25e3 nanowire emitter delivers a very high current density of -1.2 mA cm(-2) at an applied electric field of -6.33 cm(-1). The present results demonstrate In2Se3 as an important candidate for potential applications in nano/micro-electronic devices.